Michelangelo Gedichte und Briefe : In Auswahl herausgegeben von R. A. Guardini - Michelangelo Buonarroti, 1475-1564; Guardini, Romano, 1885-1968; Grasberger, Hans, 1836-1898; Guardini, Romano, 1885-1968; Hasenclever, Sophie, 1824-1892; Jacobson, Bettina, 1841-1922; Witte, Johann Heinrich Friedrich Karl, 1800-1883 (Salt Lake City, UT : Project Gutenberg, 2005)
"Michelangelo Gedichte und Briefe" by Michelangelo Buonarroti is a collection of poems and letters written in the late 16th to early 17th century. This compilation offers insights into the inner world of Michelangelo, showcasing his personal struggles, artistic ideals, and close relationships, particularly focusing on his love for the noble beauty of humanity and the art he created. The opening of this collection sets the tone for the exploration of Michelangelo's deeply personal reflections and poetic expressions. It emphasizes the nature of his poetry, primarily centered on his experiences and emotions rather than mere observations of the world around him. The introduction elaborates on Michelangelo's solitude and introspection, revealing how his artistic vision was born out of an internal struggle with passion and ideals, which, at times, hindered his ability to connect with others, even in love. Through themes of longing and the pursuit of beauty, readers are drawn into Michelangelo's complex emotional landscape as he navigates the intersections of art, beauty, and personal relationships, particularly in connection with a significant figure in his life, Vittoria Colonna. (This is an automatically generated summary.)
Release date is 2005-05-11
E-text prepared by Wallace McLean, Hagen von Eitzen, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Artists -- Correspondence; Italian poetry -- 16th century -- Translations into German; Michelangelo Buonarroti, 1475-1564. Correspondence